2005
DOI: 10.1063/1.2149172
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved analysis of the set process in an electrical phase-change memory device

Abstract: An experimental investigation was carried out on the kinetic nature of the set process in a phase change memory device by combined analyses of set voltage wave forms and time-resolved low-field resistances. As it turned out, the progress of a set process may be measured in terms of three characteristic times in sequence i.e., threshold switching time tth, incubation time for crystallization tinc, and complete set time tset. These characteristic times are supposed to demarcate, in some measure, different stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 7 publications
3
28
1
Order By: Relevance
“…[14][15][16][17][18][19] Compared to the vertical device architecture commonly employed in integrated memory devices, 3,8,20 planar devices 4,7,14-19 offer important advantages for fundamental studies. First, four-probe geometry can be easily realized in NW devices, enabling the disentanglement of metal-NW contact issues from the properties of the NW.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19] Compared to the vertical device architecture commonly employed in integrated memory devices, 3,8,20 planar devices 4,7,14-19 offer important advantages for fundamental studies. First, four-probe geometry can be easily realized in NW devices, enabling the disentanglement of metal-NW contact issues from the properties of the NW.…”
mentioning
confidence: 99%
“…In [67], the exponential voltage dependence of the delay time t d was observed for Ge 2 Sb 2 Te 4 films 90 nm thick (Fig. 24).…”
Section: Physics Of Switching and Memory Effects 567mentioning
confidence: 83%
“…5. This suggests that τ is not related to the GST phase transition but rather depends on the electrical switching time and measurement set-up parasitic effects [8]. Thus, P SET can be used as a characteristic parameter of the SET operation once the pulse amplitude is fixed, while the energy E SET provided to the cell during the same operation linearly increases with PW:…”
Section: Cell Structure and Experimental Set Upmentioning
confidence: 99%
“…From there, other results show that the progress of a SET process may be measured in terms of three characteristics times in sequence i.e., switching time t SW , incubation time for crystallization t INC , and complete SET time t SET . D.-H. Kang et al [8] demonstrated that switching time t S also depends on the applied voltage pulse, and S. Kim and H.-S. P. Wong [7] recently showed that there is a minimum SET voltage that is determined by material properties and independent on geometry, opening new studies on cell performance optimization and scaling.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation